‘LONGI TEMPORIS PRAESCRIPTIO’ JAKO ZARZUT DŁUGIEGO OKRESU POSIADANIA - Ruszkiewicz, Beata (Zeszyty Prawnicze, 2016)
‘LONGI TEMPORIS PRAESCRIPTIO’ AS A DEMURRER IN THE MATTER OF LONG POSSESSION Summary During centuries Praescriptio longi temporis has changed its meaning, requirements, application and nature, therefore, it seems to be adequate, to use it as a subject of the conference entitled “Law at the turn of the century”. This term derives from the Greek law. During the Pre-Classical Age it had its specific nature of an usual procedural privilege, granted on the basis of a long lack of action taken from the opposite party. Since the 1st century AD it had been used in Roman provinces and between peregrines. In Justinian’s era, after the combination with usucapio, it gained the acquiring nature. Praescriptio longi temporis, as a system operating according to the Greek conception, was, on the one hand, aimed at the ending of the insecurity of the relations resulting from the long-term provincial property possession, while on the other, it couldn’t lead to acquire their ownership due to the fact that they belonged to the Roman State. As the extinguishing limitation, it resembled the roman exceptio, after the defendant, and rei vindicatio, after the owner. It was set against the owner who revindicates, who would have left the provincial land unsecured for the period of 20 years, if the case had concerned subjects inhabiting different provinces (inter absentes) and for the period of 10 years, if the sides had inhabited the same province (inter praesentes). At the turn of the 3rd and 4th century AD it gained the acquiring effectiveness that convinced Justinian to conduct a fundamental reform by which virtue, from the combination of usucapio and longi temporis praescriptio, ordinary acquisitive prescription originated and extraordinary acquisitive prescription was introduced – longissimi temporis praescriptio.